Organic Photovoltaics III 2003
DOI: 10.1117/12.452414
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a novel -D-B-A-B- block copolymer system for potential light harvesting applications

Abstract: Supra-molecular and nano-structured electro-active polymers are potentially useful for developing variety inexpensive and flexible shaped opto-electronic devices. In the case of organic photovoltaic materials or devices, for instance, photo induced electrons and holes need to be separated and transported in organic acceptor (A) and donor (D) phases respectively. In this paper, preliminary results of synthesis and characterizations of a coupled block copolymers containing a conjugated donor block (RO-PPV), a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Though this approach included pendant fullerenes in the acceptor block, other acceptor block structures based on n-type conjugated polymers were reported recently. 216 In another approach, it was recently demonstrated that nanometer-sized polymer spheres could be obtained via a miniemulsion preparation (Fig. 20).…”
Section: B Concepts For Nanomorphology Controlmentioning
confidence: 99%
“…Though this approach included pendant fullerenes in the acceptor block, other acceptor block structures based on n-type conjugated polymers were reported recently. 216 In another approach, it was recently demonstrated that nanometer-sized polymer spheres could be obtained via a miniemulsion preparation (Fig. 20).…”
Section: B Concepts For Nanomorphology Controlmentioning
confidence: 99%